Community Centres as Sites of Translation: Placemaking in Edinburgh - Liao, Min-Hsiu; Strani, Katerina; Johnstone, Eilidh (Text Matters: A Journal of Literature, Theory and Culture, 2025)
This article presents a research project comprising a series of community initiatives in Edinburgh, a city which displays a disproportionately English-heavy linguistic profile, despite the cosmopolitan influences of both migration and tourism. Our case study created sites that can be conceptualised as translation spaces, where the dominant direction of translation is challenged and critiqued, or even temporarily reversed to reclaim urban space. The research team collaborated with local libraries and community centres to establish several sites of translation. This paper focuses on one key site: a series of art workshops led by refugee artists. Drawing upon the concept of translation space from Translation Studies, we explicitly thematised the role of language(s) and language exchange in these microsites, so that language traffic and dynamics could be observed, discussed, and challenged. In this way, this article contributes to the study of translation space in two aspects. Firstly, it demonstrates how contested language spaces can be analysed through translation practices manifested in various material modes, including interpretations (or, oral translations) provided by participants for one another in art workshops, and intersemiotic translation, from feelings through languages to artwork. Secondly, the paper reflects on how creating such microsites of translation can contribute to resisting the dominant direction of translation in the city.